Cornea Findings of Spectral Domain Anterior Segment Optical Coherence Tomography in Uveitic Eyes of Various Etiologies. Issue 10 (October 2019) - Hashida, Noriyasu; Asao, Kazunobu; Maruyama, Kazuichi; Nishida, Kohji
Abstract : Purpose: To evaluate the morphologic appearance of keratic precipitates (KPs) with spectral domain anterior segment optical coherence tomography (AS-OCT) for the diagnosis of uveitic eyes of various etiologies. Methods: In all, 153 eyes of 153 patients with different types of uveitis were examined to investigate the morphologic appearance of KPs. The study included 63 eyes with herpetic iridocyclitis/endotheliitis, 58 eyes with ocular sarcoidosis, 5 eyes with Fuchs heterochromic iridocyclitis, and 27 eyes with masquerade syndrome with primary intraocular lymphoma (PIOL). AS-OCT was used to analyze the different KP types among various uveitic groups. Results: KPs were observed in 30 eyes (51.7%) from the ocular sarcoidosis group and in 15 eyes (55.6%) from the PIOL group. In the herpetic iridocyclitis/endotheliitis group, all cases showed KPs (16 cases were positive for herpes simplex virus, 22 cases for varicella zoster virus, and 27 cases for cytomegalovirus). The reflectivity and morphology of the KPs in the AS-OCT images demonstrated different patterns depending on the causative virus. Hemispheric and relatively large KPs were observed in ocular sarcoidosis cases. KPs with Fuchs heterochromic iridocyclitis appeared as small dots. By contrast, relatively high-intensity and dense KPs were observed in PIOL cases. The morphologic features of the KPs in different types of uveitis also showed other patterns such as hemispheric and rectangular-shaped KPs protruding from the retrocornea. Conclusions: AS-OCT images showed characteristic and specific morphological patterns. AS-OCT examination is a noninvasive and repeatable method for the diagnosis of uveitis by evaluating the morphologies of KPs and treatment effectiveness.